Coconut husk to reducing sugar conversion using combined ultrasound and surfactant aided subcritical water - Zuhroh, Saiyyidah Tus; Fatmawati, Akbarningrum; Widjaja, Arief (Jurnal Rekayasa Proses, 2022)
The first purpose of this study was to investigate the effect of operating variables and surfactant concentration in subcritical water to after ultrasonic process on the sugar-producing yield from coconut husk. The second purpose was to obtain the optimum operating condition of the subcritical water process. The sonication before the subcritical water process was done by dispersing 40 mesh coconut husk powder in water at 60°C, and 35 kHz. The effect of sonication time was studied by comparing the material crystallinity and composition after being treated for 30 minutes. In this research, the optimization was done by using a Box-Behnken response surface methodology (RSM) experimental design with 3 factors (temperature, time, and surfactant concentration). The designed lower and upper levels were 130°C and 170°C, 40, and 80 minutes, as well as 1 and 3% (w). The results showed that the quadratic response surface model predicted the maximum reducing sugar yield to be 12.0%, which was achieved at the optimum condition of 170°C, 77.5 minutes, and 2.3% SDS surfactant addition. The experiment run at the obtained optimum condition resulted in a reducing sugar yield of 11.7%, which was close to that obtained from the model prediction.